Energy, inflation and market power: Excess pass-through in France - Axelle Arquié; Malte Thie (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2023)
We explore how, in the French manufacturing sector, producer prices vary with market power during a severe episode of energy price hikes (between January 2020 and February 2023). Our work provides some empirical evidence in favor of a role for firms' market power in explaining inflation, and in favor of the "sellers' inflation" hypothesis (Weber and Wasner (2023)): in less competitive sectors, firms could use the energy price hike to increase their prices more than warranted by actual changes in costs. Using a rich dataset on French manufacturing firms' balance sheets, we first estimate markups at the firm-level, and aggregate them at the sectoral level. We then study the response of the producer price index (PPI) to a change in spot energy prices, depending on average market power within sectors. We show that, in sectors with higher markups, prices increase relatively more: in the least competitive sector, firms pass through up to 110% of the energy shock, implying an excess pass-through of 10 percentage points. In addition, we find that the association between markup and pass-through is even higher when markup dispersion is low, consistent with the argument that firms engage in price hikes when they expect their competitors to do the same.
Keywords: E31; F4; L11; 330; Inflation; Markups